2018
DOI: 10.1111/aos.13836
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal structural analysis and vascularity index in retinal dystrophies

Abstract: Decreased choroidal vascularity was seen in eyes with retinal dystrophies. (CVI) may be a helpful tool in monitoring choroidal involvement in retinal dystrophies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The choroid vascularity index (CVI) is a useful measurement for evaluating the middle and large choroid vessels, especially in choroidal hyperfusion diseases such as central serous chorioretinopathy [ 2 ] as well as degenerative diseases such as Stargardt disease [ 16 ]. Several reports on RP have reported that CVI decreases in B-scans passing through the fovea [ 9 , 17 ]. Choroidal flow in the central 2.4 mm × 2.4 mm area was also assessed by using laser speckle flowgraphy (LSFG) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choroid vascularity index (CVI) is a useful measurement for evaluating the middle and large choroid vessels, especially in choroidal hyperfusion diseases such as central serous chorioretinopathy [ 2 ] as well as degenerative diseases such as Stargardt disease [ 16 ]. Several reports on RP have reported that CVI decreases in B-scans passing through the fovea [ 9 , 17 ]. Choroidal flow in the central 2.4 mm × 2.4 mm area was also assessed by using laser speckle flowgraphy (LSFG) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…CVI has been used to represent the choroidal vessel condition in central serous chorioretinopathy [8]. Previous studies on retinal dystrophies have revealed a decrease of CVI in comparison to that of normal controls [9]. However, these studies all focused on one B-scan passing through the fovea but did not investigate the perifoveal region, which would be more likely to be affected in RP eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Choroidal vascular changes may contribute to the primary pathology of photoreceptor and RPE in inherited retinal disorders. CVI has been recently proposed as a novel OCT-based parameter to quantify structural changes in eyes with retinal dystrophies [22].…”
Section: In Inherited Retinal Disordersmentioning
confidence: 99%
“…In a retrospective case control study, Wei et al assessed CVI in patients affected by retinitis pigmentosa (RP) (n = 17), Stargardt disease (SD) (n = 4), cone-rod dystrophy (n = 3), Best disease (n = 1), and Bietti crystalline dystrophy (n = 1) [22].…”
Section: In Inherited Retinal Disordersmentioning
confidence: 99%
“…The CVI, a ratio of LCA over TCA, has been applied to various chorioretinal diseases [10,20,21], including many inherited retinal dystrophies [12,22]. Wei et al found a decreased CVI in patients with RP, cone-rod dystrophy, Stargardt disease, Bietti crystalline dystrophym, and Best disease [22]. Recently, Iovino et al investigated the choroidal features associated with the presence of CME in eyes with RP, reporting an increased CT and decreased CVI in eyes with intraretinal fluid [12].…”
Section: Discussionmentioning
confidence: 99%